Role of Risk Factors in the Development of Myocardial Infarction in Young Men Depending on Family History - E. N., Tashkenbaeva; Tolibovna, Madjidova Gulbahor; Ismatovna, Sunnatova Gulbahor (Journal of Science in Medicine and Life, 2023)
we examined 96 men, of which 62 (27.2%) aged 35 to 45 years were identified as suffering from coronary heart disease. Each patient was interviewed in the form of a standardized survey, which included identification of CSD, including a family history of MI. Monitoring and blood pressure measurements were carried out. The most informative in terms of assessing the likelihood of developing a myocardial infarction are the following signs: age, increased concentrations of total cholesterol, triglycerides, low-density lipoproteins, death from stroke or heart attack.